Increased Levels of Circulating Angiogenic Cells and Signaling Proteins in Older Adults With Cerebral Small Vessel Disease - Kapoor, Arunima; Gaubert, Aimée; Marshall, Anisa; Meier, Irene B.; Yew, Belinda; Ho, Jean K.; Blanken, Anna E.; Dutt, Shubir; Sible, Isabel J.; Li, Yanrong; Jang, Jung Yun; Brickman, Adam M.; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Cerebral small vessel disease (SVD) is associated with increased risk of stroke and dementia. Progressive damage to the cerebral microvasculature may also trigger angiogenic processes to promote vessel repair. Elevated levels of circulating endothelial progenitor cell (EPCs) and pro-angiogenic signaling proteins are observed in response to vascular injury. We aimed to examine circulating levels of EPCs and proangiogenic proteins in older adults with evidence of SVD. Method: Older adults (ages 55-90) free of dementia or stroke underwent venipuncture and brain MRI. Flow cytometry quantified circulating EPCs as the number of cells in the lymphocyte gate positively expressing EPC surface markers (CD34+CD133+CD309+). Plasma was assayed for proangiogenic factors (VEGF-A, VEGF-C, VEGF-D, Tie-2, Flt-1). Total SVD burden score was determined based on MRI markers, including white matter hyperintensities, cerebral microbleeds and lacunes. Results: Sixty-four older adults were included. Linear regression revealed that older adults with higher circulating EPC levels exhibited greater total SVD burden (β = 1.0 x 105, 95% CI [0.2, 1.9], p = .019), after accounting for age and sex. Similarly, a positive relationship between circulating VEGF-D and total SVD score was observed, controlling for age and sex (β = .001, 95% CI [0.000, 0.001], p = .048). Conclusion: These findings suggest that elevated levels of circulating EPCs and VEGF-D correspond with greater cerebral SVD burden in older adults. Additional studies are warranted to determine whether activation of systemic angiogenic growth factors and EPCs represents an early attempt to rescue the vascular endothelium and repair damage in SVD.